Evaluation of daily online contour adaptation by radiation therapists for prostate cancer treatment on an MRI-guided linear accelerator. (March 2021) - Willigenburg, Thomas; de Muinck Keizer, Daan M.; Peters, Max; Claes, An; Lagendijk, Jan J.W.; de Boer, Hans C.J.; van der Voort van Zyp, Jochem R.N.
Highlights: Adapt-to-Shape (ATS) workflows enable high-precision MR-guided radiotherapy. Online, manual contour adaptation is a time-consuming step in the ATS workflow. Trained radiation therapists adapt contours for prostate cancer treatment. CTV contours by radiation therapists are well-suited for MR-Linac prostate cancer treatment. Abstract: Background and purpose: Magnetic resonance (MR)-guided linear accelerator (MR-Linac) systems have changed radiotherapy workflows. The addition of daily online contour adaptation allows for higher precision treatment, but also increases the workload of those involved. We train radiation therapists (RTTs) to perform daily online contour adaptation for MR-Linac treatment of prostate cancer (PCa) patients. The purpose of this study was to evaluate these prostate contours by performing an interfraction and interobserver analysis. Materials and methods: Clinical target volume (CTV) contours generated online by RTTs from 30 low-intermediate risk PCa patients, treated with 5x7.25 Gy, were used. Two physicians (Observers) judged the RTTs contours and performed adaptations when necessary. Interfraction relative volume differences between the first and the subsequent fractions were calculated for the RTTs, Observer 1, and Observer 2. Additionally, interobserver dice's similarity coefficient (DSC) for fraction 2–5 was calculated with the RTTs- and physician-adapted contours. Clinical acceptability of the RTTs contours was judged by a third observer. Results: Mean (SD) online contour adaptation time was 12.6 (±3.8) minutes and overall median (interquartile range [IQR]) relative volume difference was 9.3% (4.4–13.0). Adaptations by the observers were mostly performed at the apex and base of the prostate. Median (IQR) interobserver DSC between RTTs and Observer 1, RTTs and Observer 2, and Observer 1 and 2 was 0.99 (0.98–1.00), 1.00 (0.98–1.00), and 1.00 (0.99–1.00), respectively. Contours were acceptable for clinical use in 113 (94.2%) fractions. Dose-volume histogram (DVH) analysis showed significant CTV underdosage for one of the seven identified outliers. Conclusion: Daily online contour adaptation by RTTs is clinically feasible for MR-Linac treatment of PCa.